2012
DOI: 10.3139/146.110654
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the mechanical properties of natural asphalt-modified hot mixture

Abstract: Evaluation of the mechanical properties of natural asphalt-modified hot mixture The objective of this study is to evaluate the usage of natural asphalt in hot mix asphalt by means of determining the Marshall stability, stiffness modulus, indirect tensile strength, and dynamic creep tests. Natural asphalt, which consists of 17 % asphalt fraction and 83 % mineral fraction, was obtained from Syrian. The optimum bitumen content was determined to be 1 % lower for natural asphalt-modified mixtures compared to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
1
3
0
1
Order By: Relevance
“…ITS values of 20NA, 35NA and 50NA mixtures were 64%, 97% and 180% higher than the pure mixture, respectively. It is seen that the use of natural asphalt can increase the tensile strength of the mixtures up to 2 times with the same trend as other studies in the literature (12,6,4,9). The 4SBS mixture has 37% higher ITS value than that of the pure mixture.…”
Section: Its = 2pmax / πTd (1)supporting
confidence: 82%
See 1 more Smart Citation
“…ITS values of 20NA, 35NA and 50NA mixtures were 64%, 97% and 180% higher than the pure mixture, respectively. It is seen that the use of natural asphalt can increase the tensile strength of the mixtures up to 2 times with the same trend as other studies in the literature (12,6,4,9). The 4SBS mixture has 37% higher ITS value than that of the pure mixture.…”
Section: Its = 2pmax / πTd (1)supporting
confidence: 82%
“…It has been determined that the fatigue life, rutting resistance and high temperature performances of bituminous hot mixtures prepared with gilsonite modified binders have increased [10,11]. Hot bituminous mixtures prepared by natural asphalt which consists of 17% asphalt fraction and 83% mineral fraction was found to be higher stiffness modulus and also resistance to permanent deformation compared to control mixtures [12]. It was concluded that the use of Gilsonite is useful for constructing asphalt mixture with harder bitumen in order to have more rutting resistance and better load distribution within structure and as a result less stresses in pavement structure [13].…”
Section: Introductionmentioning
confidence: 99%
“…Kök et al [153] used a NA composed of 17 wt% asphalt fraction and 83 wt% mineral fraction to modify an asphalt mixture. They used an AC 190 pen as an asphalt binder.…”
Section: Oil Sands and Othersmentioning
confidence: 99%
“…Ал кейбір зерттеулер [9] 8,33% модификаторы бар битум құмымен модификацияланған қоспалардың Юнг модулі мұнай битумының қоспасымен салыстырғанда жоғары екенін көрсетті. Басқа зерттеулер шайырлы құмды негізгі қабат немесе дұрыс қоспа құрамы бар тозу қабаты ретінде пайдалануға болатынын көрсетті [10].…”
Section: нефтехимияunclassified